Securitizing immigration the politics of risk in the EU - Munster, Rens van 1977- (Palgrave studies in international relations, 2009)
"Securitizing Immigration deals with the growing concern for immigration as a matter of security at the EU level. It combines an analysis of the way bureaucratic and political processes have interacted in the integration process with an analysis of how these practices are located in a context shaped by the preoccupation with risk"--Provided by publisher